Hydrogen Recovery from Waste Gas Streams to Feed (High-Temperature Pem) Fuel Cells: Environmental Performance Under a Life-Cycle Thinking Approach - Abejon-Elias, R (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Fossil fuels are being progressively substituted by a cleaner and more environmentally friendly form of energy, where hydrogen fuel cells stand out. However, the implementation of a competitive hydrogen economy still presents several challenges related to economic costs, required infrastructures, and environmental performance. In this context, the objective of this work is to determine the environmental performance of the recovery of hydrogen from industrial waste gas streams to feed high-temperature proton exchange membrane fuel cells for stationary applications. The life-cycle assessment (LCA) analyzed alternative scenarios with different process configurations, considering as functional unit 1 kg of hydrogen produced, 1 kWh of energy obtained, and 1 kg of inlet flow. The results make the recovery of hydrogen from waste streams environmentally preferable over alternative processes like methane reforming or coal gasification. The production of the fuel cell device resulted in high contributions in the abiotic depletion potential and acidification potential, mainly due to the presence of platinum metal in the anode and cathode. The design and operation conditions that defined a more favorable scenario are the availability of a pressurized waste gas stream, the use of photovoltaic electricity, and the implementation of an energy recovery system for the residual methane stream. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.